The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0037-86822008000500001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, epidemiological and laboratory aspects of patients with American cutaneous leishmaniasis in the State of Pernambuco

Abstract: The diagnosis for American cutaneous leishmaniasis is based on an association of clinical, epidemiological and laboratory characteristics. The present study identified the circulating species of Leishmania in the State of Pernambuco, described its clinical-epidemiological characteristics and diagnosed the disease. Nineteen patients presenting active lesions who had been diagnosed through clinical evaluation and laboratory tests were selected. The tests included direct investigation, in vitro culturing, Montene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 24 publications
5
17
1
4
Order By: Relevance
“…This result was also found in other studies [11][12][13] . However, from 2001 to 2006, the number of reported cases in the City of Governador Valadares was similar for both genders, as 127 cases of ATL were male patients (52.7%) and 114 (47.3%) cases were female patients 14 .…”
Section: Discussionsupporting
confidence: 91%
“…This result was also found in other studies [11][12][13] . However, from 2001 to 2006, the number of reported cases in the City of Governador Valadares was similar for both genders, as 127 cases of ATL were male patients (52.7%) and 114 (47.3%) cases were female patients 14 .…”
Section: Discussionsupporting
confidence: 91%
“…The combination of different molecular approaches allows appropriate parasite identification in areas where sympatric circulation of several Leishmania species is a problem (Bensoussan et al 2006, Tojal da Silva et al 2006. Our study demonstrated a PCR positivity of 89%, which is lower than has been described in other areas (Pirmez et al 1999, Gomes et al 2008, Reis et al 2008). However, our results are consistent with a previous study in the same area that reported a positivity of 88.3% for PCR performed with DNA obtained from fresh-frozen lesion biopsies and positivities of 87% and 85.7% for PCR performed with DNA obtained from biopsy imprints on filter paper in two independent laboratories (Romero et al 2009).…”
Section: Discussioncontrasting
confidence: 43%
“…These rates are higher than those obtained by Silveira et al (7) for cutaneous form ATL (59.4%) and by Curti et al (14) for cutaneous form ATL (65.1%) in the same area. Murback et al (27) observed a rate of 58.8% for positive direct examination in Mato Grosso do Sul State, whereas Reis et al (29) observed a rate of 58% for positive direct examination in Pernambuco State. These variations may be due to several factors such as Leishmania species, parasite load, quality of the material collected, site of the lesion where the parasite is investigated, the number of microscopic fields and slides examined, and experience of the technician (30) .…”
Section: Discussionmentioning
confidence: 99%